2005
DOI: 10.1093/deafed/eni036
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Visual Communication on the Intersubjective Development of Early Parent-Child Interaction With 18- to 24-Month-Old Deaf Toddlers

Abstract: This article presents a study that examined the impact of visual communication on the quality of the early interaction between deaf and hearing mothers and fathers and their deaf children aged between 18 and 24 months. Three communication mode groups of parent-deaf child dyads that differed by the use of signing and visual-tactile communication strategies were involved: (a) hearing parents communicating with their deaf child in an auditory/oral way, (b) hearing parents using total communication, and (c) deaf p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 62 publications
1
42
0
Order By: Relevance
“…As they expected, Loots et al (2005) found higher intersubjectivity levels in parents who used AAC compared with parents who used spoken language. Swanwick and Watson (2007) described similar results.…”
Section: Interventions and Their Effectssupporting
confidence: 74%
See 1 more Smart Citation
“…As they expected, Loots et al (2005) found higher intersubjectivity levels in parents who used AAC compared with parents who used spoken language. Swanwick and Watson (2007) described similar results.…”
Section: Interventions and Their Effectssupporting
confidence: 74%
“…The term "intersubjectivity" was not used for the study variables in most of these studies (except for Loots, Devisé, & Jacquet, 2005;Saliés & Starosky, 2008). Although other authors did not explicitly measure "intersubjectivity", they measured variables that could be attributed to one of the layers of intersubjectivity that Trevarthen described.…”
Section: Intersubjectivity Measuresmentioning
confidence: 99%
“…For a profoundly deaf baby before cochlear implantation, this third side of the triangle of reference is not fully accessible except through vision. This means that without guidance as to where to position the object of references [26,27] it will be difficult for an adult inexperienced in sign to make their communication contingent and meaningful to the child; and it will be equally difficult for the child to integrate visual communication in parallel with visual attention to the object or event. This situation can be further complicated by the adult's attempts to engage the child: instead of following what is occupying the baby's attention and thoughts, the baby is expected to interpret what is the adult's focus of interest, which is impossible for a young infant [28].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the intersubjective development of children with deafness who have hearing parents and those who have parents with deafness support the importance of social partners' adapting their communication strategies to the individual needs of a child with sensory disabilities. In a 2005 study by Loots, Devisé and Jacquet (2005), for example, the highest intersubjective quality was observed in interpersonal communication between children with deafness and parents using sign language and sequential visual interaction strategies. Parents who themselves had deafness used these types of adapted strategies more spontaneously (Jamieson, 1994).…”
mentioning
confidence: 98%
“…Some children display delays in affective attunement (Jamieson, 1994;Preisler, 1995). Absence of symbolic communication has also been described for groups of people with auditory and visual impairments, as well as for children with deafblindness (Bruce, 2005;Loots, Devisé, & Jacquet, 2005).…”
mentioning
confidence: 99%